2023
DOI: 10.1136/bmjopen-2022-067065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of taste and smell dysfunction in mild and asymptomatic COVID-19 patients during Omicron prevalent period in Shanghai, China: a cross-sectional survey study

Abstract: ObjectivesCOVID-19, which is caused by SARS-CoV-2, is a severe threat to human health and the economy globally. This study aimed to investigate the prevalence of taste and/or smell dysfunction and associated risk factors in mild and asymptomatic patients with Omicron infection in Shanghai, China.DesignThis was a questionnaire-based cross-sectional study.SettingCOVID-19 patients at the makeshift hospital in the Shanghai World Expo Exhibition and Convention Centre were recruited from March to April 2022.Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(111 reference statements)
1
3
0
Order By: Relevance
“…Approximately 25% of the participants reported sensory change, and only around 5% reported complete loss of taste or smell, compared to the 40–60% experiencing smell or taste changes in a meta-analysis of studies based on objective measures [ 4 ]. However, this finding is consistent with more recent evaluations of smell and taste loss in COVID-19 patients [ 55 , 56 ], with evidence suggesting that the occurrence of smell and taste changes has decreased in more recent variants of COVID-19 [ 57 ]. For example, an analysis of 12 reports of patients infected with COVID-19 during the Omicron wave had a pooled estimated olfactory dysfunction of only 13% [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Approximately 25% of the participants reported sensory change, and only around 5% reported complete loss of taste or smell, compared to the 40–60% experiencing smell or taste changes in a meta-analysis of studies based on objective measures [ 4 ]. However, this finding is consistent with more recent evaluations of smell and taste loss in COVID-19 patients [ 55 , 56 ], with evidence suggesting that the occurrence of smell and taste changes has decreased in more recent variants of COVID-19 [ 57 ]. For example, an analysis of 12 reports of patients infected with COVID-19 during the Omicron wave had a pooled estimated olfactory dysfunction of only 13% [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, increased co-morbidities and prescription drugs in elderly individuals could additionally impact the clinical course of OD [69,70]. Additionally, fever, cough, expectoration, stuffy nose, nasal congestion, purulent nasal, sore throat, foul breath, and xerostomia (oral dryness) are typical symptoms observed in patients with OD and patients who have suffered from three or more upper respiratory symptoms were prone to experience OD [71].…”
Section: Risk Factors Of Odmentioning
confidence: 99%
“…Based on the findings of multivariate analysis, risk factors associated with reporting a loss of smell were younger age [67,68], asthma [72], emphysema [73], female sex [29,[46][47][48][49], or cough [49,71,74]. A clinical risk category approach by Johnson et al (2022) [72], revealed the high-risk patients and individuals who were most likely to get serious infections and poor clinical outcomes.…”
Section: Risk Factors Of Odmentioning
confidence: 99%
“…About 1 in 5 people with COVID-19 report persistent (i.e., lasting more than 10 days) COVID-19-related anosmia (loss of the sense of smell), hyposmia (reduced sense of smell) or parosmia (distorted sense of smell; e.g., Chary et al, 2020 ; Chiesa-Estomba et al, 2020 ; Antolín-Amérigo et al, 2021 ; Printza et al, 2021 ). A similar proportion of people with COVID-19 report ageusia (loss of the sense of taste), hypogeusia (reduced sense of taste) or dysgeusia (altered perception of taste), with many people reporting both smell and taste impairment ( Wang et al, 2023 ). Even though the prevalence of COVID-19-associated smell and taste impairment decreased with later variants of the virus ( Boscolo-Rizzo et al, 2022 ), it still appears significant for the Omicron variant at around 12% in people with European ancestry ( von Bartheld and Wang, 2023 ).…”
Section: Introductionmentioning
confidence: 99%